Comparison of Anticoagulation Quality between Acenocoumarol and Warfarin in Patients with Mechanical Prosthetic Heart Valves: Insights from the Nationwide PLECTRUM Study - Danilo Menichelli; Daniela Poli; Emilia Antonucci; Vittoria Cammisotto; Sophie Testa; Pasquale Pignatelli; Gualtiero Palareti; Daniele Pastori; the Italian Federation of Anticoagulation Clinics (FCSA) (Molecules, 2021)
Vitamin K antagonists are indicated for the thromboprophylaxis in patients with mechanical prosthetic heart valves (MPHV). However, it is unclear whether some differences between acenocoumarol and warfarin in terms of anticoagulation quality do exist. We included 2111 MPHV patients included in the nationwide PLECTRUM registry. We evaluated anticoagulation quality by the time in therapeutic range (TiTR). Factors associated with acenocoumarol use and with low TiTR were investigated by multivariable logistic regression analysis. Mean age was 56.8 ± 12.3 years; 44.6% of patients were women and 395 patients were on acenocoumarol. A multivariable logistic regression analysis showed that patients on acenocoumarol had more comorbidities (i.e., ≥3, odds ratio (OR) 1.443, 95% confidence interval (CI) 1.081–1.927, p = 0.013). The mean TiTR was lower in the acenocoumarol than in the warfarin group (56.1 ± 19.2% vs. 61.6 ± 19.4%, p < 0.001). A higher prevalence of TiTR (<60%, <65%, or <70%) was found in acenocoumarol users than in warfarin ones (p < 0.001 for all comparisons). Acenocoumarol use was associated with low TiTR regardless of the cutoff used at multivariable analysis. A lower TiTR on acenocoumarol was found in all subgroups of patients analyzed according to sex, hypertension, diabetes, age, valve site, atrial fibrillation, and INR range. In conclusion, anticoagulation quality was consistently lower in MPHV patients on acenocoumarol compared to those on warfarin.